How Specific Signaling Pathways Like Wnt, Notch, and Hedgehog Regulate Cancer Stem Cells, and Potential Therapies Targeting These Pathways - Shahid , Sameen; Shah, Syeda Hina; Rahman , Atiqa; Advani, Rahul Sagar; Shiblee, Syeda Areeba; Adeel-Ur-Rehman; Gul, Hassam (Indus Journal of Bioscience Research, 2025)
This study investigates the roles of Wnt, Notch, and Hedgehog signaling pathways in the regulation of cancer stem cells (CSCs) and evaluates the effects of their inhibition on CSC properties, including self-renewal, proliferation, and resistance to conventional therapies. Established human cancer cell lines from colorectal, breast, and glioblastoma cancers were treated with specific inhibitors targeting these pathways. The cell lines were chosen based on their association with CSC-like populations and their responsiveness to signaling pathway inhibition. Flow cytometry was used to quantify the CSC population, while Western blotting analyzed the activation of β-catenin, NICD, and GLI proteins specific to Wnt, Notch, and Hedgehog pathways. Gene expression was assessed via quantitative PCR (qPCR) for stemness markers such as Oct4, Nanog, and Sox2. The MTT and clonogenic assays were employed to assess cell viability and self-renewal, respectively. One-way analysis of variance (ANOVA) revealed a significant difference in CSC populations and pathway activation following treatment with pathway inhibitors, with the Wnt inhibitor showing the most pronounced effect (p = 0.003). Post-hoc Tukey’s test confirmed significant differences between the control and treated groups, with the Wnt inhibitor reducing the CSC population most significantly. These findings underscore the potential of targeting the Wnt, Notch, and Hedgehog pathways for the development of novel cancer therapies aimed at eradicating CSCs and overcoming resistance to treatment. However, further studies are needed to explore combination therapies and clinical applicability.